2016
DOI: 10.1158/0008-5472.can-16-1162
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Natural Killer Cell Receptor Allele That Prolongs Survival of Cytomegalovirus-Positive Glioblastoma Patients

Abstract: By affecting immunological presentation, the presence of cytomegalovirus in some glioblastomas may impact progression. In this study, we examined a hypothesized role for natural killer (NK) cells in impacting disease progression in this setting. We characterized 108 glioblastoma patients and 454 healthy controls for HLA-A,-B,-C, NK-cell KIR receptors, and CMV-specific antibodies and correlated these metrics with clinical parameters. Exome sequences from a large validation set of glioblastoma patients and contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…Although early preclinical data suggest that CMV-based vaccines can be effective in models of prostate cancer, melanoma, and squamous cell carcinoma (17)(18)(19)(20)(21)(22)(23), it has also been proposed that latent CMV infection of tumors may contribute to tumor progression in patients (34)(35)(36). Indeed, CMV has been found in several human cancers, with unknown consequences (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). The best-studied association of cancer and CMV is with glioblastoma, in which antiviral therapy may delay tumor growth (39,(47)(48)(49)(50)(51).…”
mentioning
confidence: 99%
“…Although early preclinical data suggest that CMV-based vaccines can be effective in models of prostate cancer, melanoma, and squamous cell carcinoma (17)(18)(19)(20)(21)(22)(23), it has also been proposed that latent CMV infection of tumors may contribute to tumor progression in patients (34)(35)(36). Indeed, CMV has been found in several human cancers, with unknown consequences (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). The best-studied association of cancer and CMV is with glioblastoma, in which antiviral therapy may delay tumor growth (39,(47)(48)(49)(50)(51).…”
mentioning
confidence: 99%
“… 65 We recently demonstrated that GBM had a differentiating effect on NK cells indicated by higher fractions expressing CD57, CD16 and NKG2D in GBM patients that was further augmented by HCMV infection. 66 The CD57 + mature NK cells are potent killers but exhibit replicative senescence and diminished proliferation 67 possibly explaining their reduced numbers in the blood of seropositive GBM patients. HCMV proteins inhibit class I HLA expression 32-34 that would result in loss of engagement of iKIRs specific for class I HLA ligands, effectively lowering the threshold for NK-cell activation against infected cells.…”
Section: Discussionmentioning
confidence: 99%
“… 65 Indeed, seropositive GBM patients carrying the activating KIR2DS4*00101 allele in the context of specific HLA-C1/C2 ligands had increased HCMV matured NK cells with conceivably potent cytotoxicity that contributed to substantially attenuated disease progression. 66 Thus, under these conditions, NK cells can also contribute to killing HCMV infected tumor cells, especially if tagged by anti-HCMV IgG. Their activation may contribute to the release of IFNγ that has potential to reverse the tumor microenvironment from immunosuppressive to pro-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KIR2DS2+ and KIR2DS4+ are more potent killers that bulk NK cells in glioblastoma cells (35). Remarkably, CMV impacts disease progression in glioblastoma and the KIR allele KIR2DS4 * 00101 is an independently prognostic of prolonged survival (56). Hence, the transfer of KIR2DS4 * 00101 NK cells could specifically improve prognosis of glioma patients.…”
Section: Memory Nk Cellsmentioning
confidence: 99%